• Решите, пожалуйста !
    [tex]5*(-2)^5[/tex]
    [tex]-3*(-5)^2[/tex]
    [tex]- \frac{1}{6} * (-3)^3[/tex]
    [tex] \frac{2}{5} * (-2\frac{1}{2}) ^3 [/tex]

Ответы 2

  • спасибо огромное!
    • Автор:

      alyssa
    • 5 лет назад
    • 0
  • 5*(-2)^5=5*(-32)=-160-3*(-5)^2=-3*25=-75-1/6*(-3)^3=-1/6*(27)=-9/2=-4,52/5*(-5/2)^3=2/5*(-125/9)=-50/9
  • Добавить свой ответ

Еще вопросы

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years